Pembıasaan Lıterası Fınansıal Pada Sıswa Sekolah Melaluı Program ‘’M1 Smart’’ Bekal Hıdup Dı Era Socıety 5.0 - Rosita Nur khoti’ah; Fitri Puji Rahmawati (Elementary Teacher Education Program, Majalengka University, 2024)
Abstrak This research aims to discuss the habit of financial literacy in elementary schools through M1 Smart. Financial literacy education is a person's activity in applying, understanding and managing information to make financial decisions. Financial literacy education can be taught from an early age to provide knowledge and skills for life in the era of society 5.0. This research was conducted as qualitative research. Data collection was carried out through interviews, direct observation and document analysis. Test the validity of the data using source triangulation and technical triangulation. Data analysis techniques by collecting data, data reduction, data presentation and conclusions. The research subjects included teachers in charge of M1 Smart, BUMS and students of SD Muhammadiyah 1 Ketelan Surakarta and was carried out on location. The research results show that; Implementing financial literacy habits through the M1 Smart program can provide a positive attitude for students in transaction activities, including in the canteen, library, UKS, cooperatives and BUMS, and motivate students to save and save. In the era of society 5.0, students will be able to use technology more easily because they have been equipped and trained since elementary school. Kata kunci: Financial Literacy, M1 Smart, Era 5.0